You are on page 1of 5

CALCULUS Limits (IV)

√ √
x−1− 3
1. Compute the following limit: lim
x→4 x−4
√ √
x+9− 7
2. Compute the following limit: lim
x→−2 x+2
√ √
x+7− 5
3. Compute the following limit: lim
x→−2 x+2
√ √
x−3− 1
4. Compute the following limit: lim
x→4 x−4
√ √
x+7− 2
5. Compute the following limit: lim
x→−5 x+5
√ √
x + 7 − 11
6. Compute the following limit: lim
x→4 x−4
√ √
x + 13 − 10
7. Compute the following limit: lim
x→−3 x+3
√ √
x+8− 5
8. Compute the following limit: lim
x→−3 x+3
√ √
x + 15 − 15
9. Compute the following limit: lim
x→0 x−0
√ √
x+9− 8
10. Compute the following limit: lim
x→−1 x+1

8
10. 2√1
2 15 2 5 2 10 2 11 2 2 2 1 2 5 2 7 3
√1 9. √
1
8. √1 7. √1 6. √
1
5. √
1
4. √
1
3. √
1
2. 1. 2√
1

CALCULUS Limits (IV)
Solutions:
√ √
x−1− 3
1. lim I Multiply by the conjugate radical:
x→4 x−4
√ √ √ √
x−1− 3 x−1+ 3 √
= lim ×√ √ I Use: (a − b)(a + b) = a2 − b2 and ( a)2 = a
x→4 x−4 x−1+ 3
(x − 1) − 3
= lim √ p I Remove brackets and simplify:
x→4 (x − 4)( x − 1 + 3)
x−4
= lim √ p I Simplify the common factor:
x→4 (x − 4)( x − 1 + 3)
1
= lim √ √ I Use substitution to compute the limit:
x→4 x−1+ 3
1
=√ √ I Simplify:
4−1+ 3
1
= √
2 3
√ √
x+9− 7
2. lim I Multiply by the conjugate radical:
x→−2 x+2
√ √ √ √
x+9− 7 x+9+ 7 √
= lim ×√ √ I Use: (a − b)(a + b) = a2 − b2 and ( a)2 = a
x→−2 x+2 x+9+ 7
(x + 9) − 7
= lim √ p I Remove brackets and simplify:
x→−2 (x + 2)( x + 9 + 7)
x+2
= lim √ p I Simplify the common factor:
x→−2 (x + 2)( x + 9 + 7)
1
= lim √ √ I Use substitution to compute the limit:
x→−2 x+9+ 7
1
=√ √ I Simplify:
−2 + 9 + 7
1
= √
2 7
√ √
x+7− 5
3. lim I Multiply by the conjugate radical:
x→−2 x+2
√ √ √ √
x+7− 5 x+7+ 5 √
= lim ×√ √ I Use: (a − b)(a + b) = a2 − b2 and ( a)2 = a
x→−2 x+2 x+7+ 5
(x + 7) − 5
= lim √ p I Remove brackets and simplify:
x→−2 (x + 2)( x + 7 + 5)
x+2
= lim √ p I Simplify the common factor:
x→−2 (x + 2)( x + 7 + 5)
1
= lim √ √ I Use substitution to compute the limit:
x→−2 x+7+ 5
1
=√ √ I Simplify:
−2 + 7 + 5

CALCULUS Limits (IV)
1
= √
2 5
√ √
x−3− 1
4. lim I Multiply by the conjugate radical:
x→4 x−4
√ √ √ √
x−3− 1 x−3+ 1 √
= lim ×√ √ I Use: (a − b)(a + b) = a2 − b2 and ( a)2 = a
x→4 x−4 x−3+ 1
(x − 3) − 1
= lim √ p I Remove brackets and simplify:
x→4 (x − 4)( x − 3 + 1)
x−4
= lim √ p I Simplify the common factor:
x→4 (x − 4)( x − 3 + 1)
1
= lim √ √ I Use substitution to compute the limit:
x→4x−3+ 1
1
=√ √ I Simplify:
4−3+ 1
1
= √
2 1
√ √
x+7− 2
5. lim I Multiply by the conjugate radical:
x→−5 x+5
√ √ √ √
x+7− 2 x+7+ 2 √
= lim ×√ √ I Use: (a − b)(a + b) = a2 − b2 and ( a)2 = a
x→−5 x+5 x+7+ 2
(x + 7) − 2
= lim √ p I Remove brackets and simplify:
x→−5 (x + 5)( x + 7 + 2)
x+5
= lim √ p I Simplify the common factor:
x→−5 (x + 5)( x + 7 + 2)
1
= lim √ √ I Use substitution to compute the limit:
x→−5 x+7+ 2
1
=√ √ I Simplify:
−5 + 7 + 2
1
= √
2 2
√ √
x + 7 − 11
6. lim I Multiply by the conjugate radical:
x→4 x−4
√ √ √ √
x + 7 − 11 x + 7 + 11 √
= lim ×√ √ I Use: (a − b)(a + b) = a2 − b2 and ( a)2 = a
x→4 x−4 x + 7 + 11
(x + 7) − 11
= lim √ p I Remove brackets and simplify:
x→4 (x − 4)( x + 7 + 11)
x−4
= lim √ p I Simplify the common factor:
x→4 (x − 4)( x + 7 + 11)
1
= lim √ √ I Use substitution to compute the limit:
x→4 x + 7 + 11
1
=√ √ I Simplify:
4 + 7 + 11

CALCULUS Limits (IV)
1
= √
2 11
√ √
x + 13 − 10
7. lim I Multiply by the conjugate radical:
x→−3 x+3
√ √ √ √
x + 13 − 10 x + 13 + 10 √
= lim ×√ √ I Use: (a − b)(a + b) = a2 − b2 and ( a)2 = a
x→−3 x+3 x + 13 + 10
(x + 13) − 10
= lim √ p I Remove brackets and simplify:
x→−3 (x + 3)( x + 13 + 10)
x+3
= lim √ p I Simplify the common factor:
x→−3 (x + 3)( x + 13 + 10)
1
= lim √ √ I Use substitution to compute the limit:
x→−3 x + 13 + 10
1
=√ √ I Simplify:
−3 + 13 + 10
1
= √
2 10
√ √
x+8− 5
8. lim I Multiply by the conjugate radical:
x→−3 x+3
√ √ √ √
x+8− 5 x+8+ 5 √
= lim ×√ √ I Use: (a − b)(a + b) = a2 − b2 and ( a)2 = a
x→−3 x+3 x+8+ 5
(x + 8) − 5
= lim √ p I Remove brackets and simplify:
x→−3 (x + 3)( x + 8 + 5)
x+3
= lim √ p I Simplify the common factor:
x→−3 (x + 3)( x + 8 + 5)
1
= lim √ √ I Use substitution to compute the limit:
x→−3 x+8+ 5
1
=√ √ I Simplify:
−3 + 8 + 5
1
= √
2 5
√ √
x + 15 − 15
9. lim I Multiply by the conjugate radical:
x→0 x−0
√ √ √ √
x + 15 − 15 x + 15 + 15 √
= lim ×√ √ I Use: (a − b)(a + b) = a2 − b2 and ( a)2 = a
x→0 x−0 x + 15 + 15
(x + 15) − 15
= lim √ p I Remove brackets and simplify:
x→0 (x − 0)( x + 15 + 15)
x−0
= lim √ p I Simplify the common factor:
x→0 (x − 0)( x + 15 + 15)
1
= lim √ √ I Use substitution to compute the limit:
x→0 x + 15 + 15
1
=√ √ I Simplify:
0 + 15 + 15

CALCULUS Limits (IV)
1
= √
2 15
√ √
x+9− 8
10. lim I Multiply by the conjugate radical:
x→−1 x+1
√ √ √ √
x+9− 8 x+9+ 8 √
= lim ×√ √ I Use: (a − b)(a + b) = a2 − b2 and ( a)2 = a
x→−1 x+1 x+9+ 8
(x + 9) − 8
= lim √ p I Remove brackets and simplify:
x→−1 (x + 1)( x + 9 + 8)
x+1
= lim √ p I Simplify the common factor:
x→−1 (x + 1)( x + 9 + 8)
1
= lim √ √ I Use substitution to compute the limit:
x→−1 x+9+ 8
1
=√ √ I Simplify:
−1 + 9 + 8
1
= √
2 8